PERFORMA REPRODUKSI SAAT LAHIR DAN SAPIH DARI INDUK KAWIN DENGAN PEJANTAN DUROC DAN LANDRACE (Reproduction performance at birth and weaning age of sows mating with duroc and landrace studs) - Yohanes Djego; Petrus Kune; Johny Nada Kihe (JURNAL NUKLEUS PETERNAKAN, 2020)
This research aim was to know reproduction performances at birth and weaning age of the sows which were mated with Duroc and Landrace studs. The research was carried out in two breeding farms namely the Instalation of Pig Breeding, the village of Tarus, Kupang Regency and the Manise Pig Farm, Village of Oetete, Kupang City. There were two breeds of studs namely breed of Landrace and Duroc which each stud was mated to 15 breeding pigs. The method used in this research was a survey and the samples were collected purposively. Data collection were obtained when the piglets were born and weaned. The variables were the litter size and body weight at birth age and the liter size and body weight at weaning age. The data obtained was analysed using the t test (t-test). The results showed that the characters of birth litersize,birth body weight, weaning litter size and weaning weight for Duroc stud were 10.60±2.41 head, 1.95±0.18 kg/head; 10.00±2.02 head and 5.98±0.65kg/head, respectively and those charackters for Landarace stud were 9.06±2.09head, 1.98 ±0.22 kg/head; 8.93± 2.23 head and 6.20±0.28 kg/head, respectively. Results of statistical analysed showed that Duroc and Landrace studs did not effect significantly (P>0.5) for those charackters. Reproduction performances of sows that were mated with Duroc and Landrace studs for characters of birth liter size, birth weight, weaning liter size and weaning weight were relatively similar.